Repeated mild traumatic brain injury causes focal response in lateral septum and hippocampus - Rebecca Acabchuk; Denise I Briggs; Mariana Angoa-Pérez; Meghan Powers; Richard Wolferz; Melanie Soloway; Mai Stern; Lillian R Talbot; Donald M Kuhn; Joanne C Conover (Concussion, 2016)
Aim: To advance our understanding of regional and temporal cellular responses to repeated mild traumatic brain injury (rmTBI), we used a mouse model of rmTBI that incorporated acceleration, deceler...